Zakres swobody wypowiedzi artystycznej w świetle prawa karnego: brak - Ciulkin-Sarnocińska, Katarzyna (Studia Prawnoustrojowe, 2019)
The author raises the question of the scope of freedom of artistic creation in the light of Polish criminal law. Artistic creation has always been an important area of human activity. It is associated directly or indirectly with other aspects of life, including religion, culture and politics. Its progress and transformation is accompanied by constant controversy about the limits of its freedom involving debates based on the grounds of philosophy, ethics, aesthetics and the law. Despite the signifcant place of art in human life, the guarantee freedom of artistic creation is one of the youngest and least examined rights. The analysis contains three groups of issues. The frst topic is devoted to the scope of the freedom of artistic creation. The analysis was subjected to provisions conferring freedom, but also showing the limits of the range of action of the artist. The second part of the paper covers offences which they can usually prevent, i.e. the offence of defamation of religion and the offence of the public presentation of pornographic content. The third part addresses the issue of the limits of artistic freedom presented on the basis of high-profle examples of Polish lawsuits.